DAMPAK REVOLUSI INDUSTRI YANG TERCERMIN DALAM PUISI THE MAN HE KILLED KARYA THOMAS HARDY - Wijayanti, Bernita (LANTERN (Journal on English Language, Culture and Literature), 2012)
Poem is a kind of an artistic work; a work with extraordinary language, extraordinary meaning and multi-unpredictable. The Man He Killed was a poem which was written by Thomas Hardy in 1902. The purpose of research is to discuss condition and situation of the society in Industry of Revolution. The methods used were library research, struktural approach and sosiology approach. By applying the method of library research the writer tried to collect some information and other important document supporting the prosses of analysis. The structural approach used to reveal some intrinsic element of the poem with the idea inside of the poem. On the other hand, sociology approach used to see the description of the revolution Industry. The results of the analysis indicate that there are relationship between “ The Man He Killed” and the characteristic of War and impact of Revolution Industry. By this poem, Hardy wanted to share his feeling by criticizing the government.